Discurso de Benedicto XVI al cuerpo diplomático acreditado ante la Santa Sede, 9 de enero de 2007 - Alonso, Antonio (UNISCI Discussion Papers, 2007)
The article offers a brief analysis of the speech that the Holy Father makes every year to the diplomatic corps accredited to the Holy See. In it, he analyzes the world situation bringing together two perspectives, which correspond to the double nature of his position: religious leader and Chief of State. This way, in his message he does not try to defend personal or state interests, but a sacred conception of the human being who must be in the center of the development of the peoples. He denounces the dramas still open today in the international scene and pleads for a dialogue and a pacific solution to the conflicts, always seeking to satisfy the legitimate and just aspirations of each one of the implied parts, with the exception of the terrorism, a useless and perverse instrument.